B-sides, undercurrents and overtones [ peripheries to popular in music, 1960 to the present - Plasketes, George (Ashgate popular and folk music series, 2009)
There are undercurrents and peripheral taste preferences that are a defining part of our individual and collective cultural experience. Music is no exception. This book adapts the 'A-side/B-side'